Testing of Reliability and Validity of the Peninsula Health Falls Risk Assessment Tool (PHFRAT) in Acute Care: A Cross-Sectional Study - Heikkilä A; Lehtonen L; Haukka J; Havulinna S; Junttila K (Dove Medical Press, 2021)
Anniina Heikkilä,1 Lasse Lehtonen,2 Jari Haukka,3 Satu Havulinna,4 Kristiina Junttila5 1HUS Nursing Administrative Group, Helsinki University Hospital and University of Helsinki, Helsinki, Finland; 2HUS Diagnostic Center, Helsinki University Hospital and University of Helsinki, Helsinki, Finland; 3Clinicum/Department of Public Health, University of Helsinki, Helsinki, Finland; 4Department of Public Health and Welfare, Finnish Institute for Health and Welfare, Helsinki, Finland; 5Nursing Research Center, Helsinki University Hospital and University of Helsinki, Helsinki, FinlandCorrespondence: Anniina Heikkil&#x00E4HUS Nursing Administrative Group, Helsinki University Hospital and University of Helsinki, P.O. Box 705, Helsinki, FI-00029, FinlandTel +358415437870Email anniina.heikkila@hus.fiPurpose: The purpose of this study was to evaluate the validity and reliability of the Peninsula Health Fall Risk Assessment Tool (PHFRAT) in acute care in various medical specialties. The assessment has not been previously studied in acute care.Methods: The cross-sectional study was conducted in a large acute care hospital system. The retrospective medical data were used to explore the validity of the PHFRAT. The data consisted of all adult inpatients (≥ 18 age) evaluated by the PHFRAT during 2014- 2016 (n = 22,700). The Poisson regression, logistic regression, sensitivity, specificity, and the area under the ROC curve were evaluated. The data for the reliability study were collected in 2016 in twelve units by evaluating the patients (n = 359) twice using the PHFRAT. The prospective data were analyzed using Fleiss' Kappa, and the content validity index was also counted.Results: In the somatic data, the change in the risk level from low risk to high risk increases the probability of falls by a factor of 2.8 (p< 0.01). When the cut-off point was 9, sensitivity and specificity were 72% and 59%, respectively, and the area under the ROC curve was 0.67 (p< 0.01). Validity varied by medical specialties. In the validity analysis, it was not possible to calculate the statistical significance from the psychiatry data. The inter-rater reliability was 0.68 (p< 0.01).Conclusion: This study shows that the PHFRAT proved to be moderately suitable for detecting the risk of falling for adult patients admitted to somatic units in acute care. The reliability of the PHFRAT was moderate. The results indicate the need to study the PHFRAT more broadly in psychiatric care as well as some specialties in somatic care.Keywords: falls, fall risk assessment, PHFRAT, acute care